Tipifíquese una sanción para quien impidiere se constituya una huelga laboral - Trujillo Rodríguez, Erick J. (2016)
The right to strike is a second-generation Human Rights and constitutional principle that consists in Freedom Rights enshrined in the Constitution of the Republic of Ecuador, a goal that has and is protected in part by the Labor Laws, in the first Paragraph of Chapter II of collective disputes. The complexity of this research focuses on the exposure of the reasons those workers and their trade unions, associations, committees, etc. within the Labor Laws have been breached in the case of the right to strike. So the right of workers to make a legitimate claim is undermined and obscured by unfair interventions agitators. This study is dedicated to analysis of those attacks directed against workers' rights enshrined in the Constitution of the Republic of Ecuador. The analysis showed that: Within the Labor Laws states that it categorizes and punish those who impede the constitution of a labor strike, ie the agitators, since your actions are violating the rights of freedom guaranteed by the Constitution of the Republic of Ecuador, as what is set forth in paragraphs 2, 13, 17 and literal d) of section 29 all these pertaining to Article 66 which recognizes and guarantees people some of their basic and fundamental rights, and more specifically in our case protects workers' rights to associate, assemble and demonstrate freely and voluntarily. It’s necessary to sanction the violation of the Strike Right, as it can be considered existing if it is not fully protected, recognized and respected in fact and law. It needs to be criminalized and punished by the Labor Laws employees, workers and most people who have a dependent relationship with the company or factory when any of the above even try to prevent settles a labor strike stratagems dotted with violence. And finally also say that the sanction should define in the same Labor Laws with the same punishment as is imposed on the strikers who ran an illegal strike, as they have interfered with the execution of one of the fundamental rights of workers and their organizations only insofar as it constitutes a means of defending their economic interests.